COMBUSTION PERFORMANCE OF RUBBER SEED AND PALM OIL BIODIESEL FUEL BLENDS WITH ANTIOXIDANTS - ADAM, IBRAHIM KHALIL (2018)
In this study, the potential of using a nonedible biodiesel source (rubber seed oil) was explored. Rubber seed oil (RSO) is a promising nonedible source for producing a sustainable biodiesel in Malaysia because 46% of worldwide rubber production belongs to Malaysia. However, due to the lower oxidation stability of the produced biodiesel, which is the result of its higher unsaturation content (78.73%), mixing with high saturation content feedstock or an oxidation inhibiter is required. A 20, 30 and 50% v/v blends of rubber seed biodiesel (RB) or palm biodiesel (PB) and varying percentage mixtures of these two feedstocks oil biodiesel (RPB) were examined on combustion, engine performance and emissions in a 55 kW multi-cylinder diesel engine at full load conditions.